2022
DOI: 10.1101/gad.349456.122
|View full text |Cite
|
Sign up to set email alerts
|

RBM33 directs the nuclear export of transcripts containing GC-rich elements

Abstract: Although splicing is a major driver of RNA nuclear export, many intronless RNAs are efficiently exported to the cytoplasm through poorly characterized mechanisms. For example, GC-rich sequences promote nuclear export in a splicing-independent manner, but how GC content is recognized and coupled to nuclear export is unknown. Here, we developed a genome-wide screening strategy to investigate the mechanism of export of NORAD, an intronless cytoplasmic long noncoding RNA (lncRNA). This screen revealed an RNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Additionally, it is known that mRNAs with high GC content at the 5’ end of cellular mRNAs are more efficiently exported from the nucleus than mRNAs with low GC content 13 , which may need additional factors, such as GANP, to facilitate export. Recently, the RBM33 protein was shown to bind to high GC stretches on mRNAs and recruit NXF1 for their export 20 . We found that the GANP-dependent mRNAs have a lower overall GC content than the GANP-independent mRNAs including regions within the first 75 nt at the 5’ end, therefore it is possible that GANP-independent mRNAs may use small GC-rich regions to recruit mRNA export factors to mediate export independent or less dependent on GANP.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that mRNAs with high GC content at the 5’ end of cellular mRNAs are more efficiently exported from the nucleus than mRNAs with low GC content 13 , which may need additional factors, such as GANP, to facilitate export. Recently, the RBM33 protein was shown to bind to high GC stretches on mRNAs and recruit NXF1 for their export 20 . We found that the GANP-dependent mRNAs have a lower overall GC content than the GANP-independent mRNAs including regions within the first 75 nt at the 5’ end, therefore it is possible that GANP-independent mRNAs may use small GC-rich regions to recruit mRNA export factors to mediate export independent or less dependent on GANP.…”
Section: Discussionmentioning
confidence: 99%
“…In our hands, the relevance of GCcds is clearly picked up by both the Random Forest and the Lasso (Supplementary Figure 4). Importantly, we included similar features, such as overall GC content 24 , in UTRs, introns etc., alongside codon frequencies 20 and previously estimated values of codon optimality.…”
Section: Discussionmentioning
confidence: 99%
“…Co-immunoprecipitation (CoIP) was performed as previously described ( 58 ), with modifications. Three days after infection, cells were scraped in ice-cold PBS and lysed in 800 μl of lysis buffer [50 mM tris-HCl at pH 7.5, 150 mM NaCl, 1% NP-40, 0.1% sodium deoxycholate, and 2× protease inhibitor tablet (Roche)] for 30 min on ice and cleared by centrifugation at 14,000 g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%